(untitled) (Physical Education, Health and Social Sciences, 2025)
The study conducts a critical review of the development of ESG (Environmental, Social, and Governance) ideology in the context of the global banking industry. It examines the literature to systematically review the integration of environmental and social sustainability in the banking model. Green Banking is studied as a subset of the ESG ideology. Based on the existing literature and Green Banking policies & guidelines, the various dimensions of Green Banking are highlighted. Own Impact Reduction, Green Business Facilitation, and Environmental & Social Risk Management (ESRM) are discussed as part of Green Banking adoption. The study critically analyses the Pakistan banking industry by reviewing the Green Banking adoption journey. The study can provide important insights towards ESG and Green Banking adoption, especially to banks in developing countries.